Preparation and Magnetic Properties of Ultra-Fine Grained g-Ni-22Fe/Al2O3 Composite - Liu, Yin; Tao, Jun; Zheng, Linyi; Xu, Chuyang; Min, Fanfei; Zhang, Mingxu (Asian Journal of Chemistry, 2012)
Ultra-fine grained g-Ni-22Fe alloy dispersed Al2O3 matrix composites were prepared by a mechano-chemical process and subsequent combining with hot-pressing sintering of nanometer Ni-22Fe alloy/Al2O3 mixed powder. The microstructure was investigated by using XRD, TEM as well as AFM. Magnetic properties were measured with using vibrating sample magnetometer (VSM) at room temperature. The results indicated that the Ni-22Fe/Al2O3 composite possessed high densities (relative density ca. 98 %) and sub-micrometer-sized matrix dispersed with g-Ni-22Fe particles of sizes below ca. 500 nm. The composite containing the ferromagnetic Fe-22Ni alloy particles exhibited ferromagnetic properties. The specific saturation magnetization and coercivity of Ni-22Fe/Al2O3 composite are 78.8 emu g-1 of Ni-22Fe, 105Oe, respectively, which points functionally structural composite material.